(untitled) (Research, Society and Development, 2021)
There is a series of feeds aimed at cats in the pet market, amongst which extruded feeds stand out, because their manufacturing process goes through thermal treatment. Such process is the main factor for the reduction of microbial contamination, as well as the action of the water in the feed. This is responsible for controlling degradation by bacteria and fungi after the manufacturing process. After opening the packages, there are several ways and factors that lead to contamination in feed. This study aimed at assessing cat feeds for their microbioligical and brotmathological content. For this, we analyzed different kinds of cat feed in the original package and traded in bulk, with different types of classification as to their quality. The assessments consisted in finding if the nutrients of the feeds were within the minimum levels required by the Manual Pet Food Brazil (2014). Analyses were performed to determine the presence of Salmonellae spp., Eschirichia coli, coliforms at 35ºC e 45ºC, Aspergillus spp e Penicillium spp; and also, for the existence of aflatoxin in the feeds. The microbiological results showed that the feeds traded unpackaged in the city of Alfenas Minas Gerais obtained results with higher levels of contamination in relation to those traded in their original packaging. This showed that the feeds exposed to the environment may compromise their microbiological quality and endanger the pets’ health. These results prove the need of greater restrictions to the trading of feeds in bulk, so that the degradation of the product is reduced, thus preserving the quality of the feed and the safety of the cats.